2002
DOI: 10.1104/pp.102.010579
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Gravity Persistence Signal Loci in Arabidopsis Disrupt the Perception and/or Signal Transduction of Gravitropic Stimuli

Abstract: Gravity plays a fundamental role in plant growth and development, yet little is understood about the early events of gravitropism. To identify genes affected in the signal perception and/or transduction phase of the gravity response, a mutant screen was devised using cold treatment to delay the gravity response of inflorescence stems of Arabidopsis. Inflorescence stems of Arabidopsis show no response to gravistimulation at 4°C for up to 3 h. However, when gravistimulated at 4°C and then returned to vertical at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…Fukaki et al (1996a) showed that the memory or stored signal of the cold gravistimulus is retained for up to 60 min in Arabidopsis inflorescence stems. Wyatt et al (2002) have utilized this phenomenon to devise a creative screen for mutants impaired in some aspect of gravity signaling. We have shown previously that increases in InsP 3 can occur at 4°C in gravistimulated oat pulvini .…”
Section: Table VI the Development Of The Asymmetric Auxin-induced Gumentioning
confidence: 99%
See 1 more Smart Citation
“…Fukaki et al (1996a) showed that the memory or stored signal of the cold gravistimulus is retained for up to 60 min in Arabidopsis inflorescence stems. Wyatt et al (2002) have utilized this phenomenon to devise a creative screen for mutants impaired in some aspect of gravity signaling. We have shown previously that increases in InsP 3 can occur at 4°C in gravistimulated oat pulvini .…”
Section: Table VI the Development Of The Asymmetric Auxin-induced Gumentioning
confidence: 99%
“…We have shown previously that increases in InsP 3 can occur at 4°C in gravistimulated oat pulvini . Furthermore, since the sedimentation of statoliths is not impaired by cold temperature (Wyatt et al, 2002), it is clear that gravity sensing and some of the early signaling can occur in the cold. In contrast, auxin transport is dramatically decreased in the cold (Morris, 1979;Wyatt et al, 2002), and cold temperature also affects cytoskeleton and membrane dynamics (Mizuno, 1992;Orvar et al, 2000;Sangwan et al, 2001).…”
Section: Table VI the Development Of The Asymmetric Auxin-induced Gumentioning
confidence: 99%
“…Another set of potential gravity signal transducers in shoots was identified in a clever genetic screen (Wyatt et al, 2002), taking advantage of the fact that Arabidopsis inflorescence stems can perceive a gravistimulus in the cold but cannot develop a curvature response under these conditions. Amazingly, Arabidopsis inflorescence stems that have been gravistimulated at 4°C can "remember" the signal for up to 1 h in the cold, such that a curvature response will be initiated if the stem is returned to room temperature during this time period (Fukaki et al, 1996).…”
Section: How About Hypocotyls and Inflorescence Stems?mentioning
confidence: 99%
“…The gps (gravity persistence signal) mutants were isolated for a defect in their ability to develop a curvature when returned to room temperature after they were gravistimulated at 4°C. The interesting properties of these mutants suggest that the GPS loci contribute to gravity perception or signal transduction at a step that follows amyloplast sedimentation but precedes lateral auxin transport (Wyatt et al, 2002). Molecular analysis of these mutations should provide important insights into the mechanisms that control gravity signal transduction in shoot statocytes.…”
Section: How About Hypocotyls and Inflorescence Stems?mentioning
confidence: 99%
“…At low temperatures, the gravitropism of inflorescence stems is declined in Arabidopsis, although gravity perception occurs normally. 5 When Arabidopsis plants are exposed to horizontal gravitropic stimulation under cold conditions and then returned to vertical orientation at 23 C, inflorescence stems bend in response to the previous horizontal gravistimulation, and statolith sedimentation occurs normally, 5,6 indicating that cold temperatures exert its effects after gravity perception.…”
mentioning
confidence: 99%